Constitutive modelling and experimental studies of densification of porous ceramic component - Lu, Jie (2012)
Porous ceramic components have found increasing applications in recent years. These include supports and electrodes for solid oxide fuel cells which require a porous structure to allow gas transport. The fabrication and stability of these porous ceramics have become the immediate challenges as the components are required to operate in harsh environment such as high temperature. Hence, a good understanding of the constitutive law of the porous ceramic will therefore be essential to help in the design and optimization of the sintering process.